THU0513 Diagnosis of Tuberculosis Infection in Pediatric Patients Treated with Tumor Necrosis Factor Alpha Inhibitors; A Multicenter Spanish Study Comparing IGRA and Tuberculin Skin Tests. (9th June 2015) - Calzada-Hernández, J.; Anton, J.; Núñez, E.; Mellado, M.J.; Martín, F.J.; Fernández, L.; Calvo, I.; Baquero, F.; Leis, R.; Eizaguirre, F.J.; Goycochea, W.A.; Donat, E.; et al.
Abstract : Background: Inhibitors of tumor necrosis factor alpha (antiTNFα) represent a major advance in the treatment of many inflammatory-mediated diseases but are associated with an increased risk of infection, including tuberculosis (TB). In adults, the interferon γ release assays (IGRA) tests show better sensitivity and specificity than the tuberculin skin test (TST) for the diagnosis of latent TB infection (LTI) in these patients. Data in children are very scarce. Objectives: To compare the IGRA tests with TST in the diagnosis of LTI in pediatric patients before antiTNFα treatment. Methods: National multicenter retrospective-prospective cross-sectional study including children and adolescents affected with rheumatic or inflammatory diseases in whom LTI screening is performed simultaneously with TST and at least one IGRA test (mostly QuantiFERON®-TB Gold In-Tube, QFT-G) prior to starting antiTNFα treatment. Patients with history of TB infection or previous antiTNFα treatment will be excluded. To maximize sensitivity, any positive result was taken as evidence for LTI. Results: Overall, 142 patients (65 boys, 45.8%) from 12 Spanish hospitals were included; 76 affected with rheumatic diseases, 54 with inflammatory bowel disease, 11 with pars planitis and 1 patient with psoriasis. None of them were BCG-vaccinated nor showed any risk factors for LTI at assessment. The mean (SD) age at diagnosis and at LTI screening were 7.9 (4.8) and 9.8 (4.3) years, respectively. Along the 3 months before LTI screening, 52 (36.6%), 100 (70.4%) and 43 (30.3%) patients had been treated with steroids, DMARDs and steroids+DMARDs, respectively. Four patients tested positive for LTI (2.8%, 95%CI 0.1-5.5; see Table ). The level of agreement between TST and IGRA tests was fair (weighted Cohen's kappa coefficient: 0.39; 95%CI: 0-0.94). The sensitivity for diagnosing LTI was 0.5 for TST and 0.75 for IGRA tests. In five patients the QFT-G tested indeterminate. No differences were found in gender, age, treatment variables or acute phase reactants among patients with indeterminate QFT-G and the rest. Conclusions: TST and QFT-G showed a fair agreement in the diagnosis of LTI in non-BCG-vaccinated patients without known risk factors for TB in Spain. Our data support current recommendations regarding the simultaneous use of TST and an IGRA test before antiTNFα treatment in order to maximize sensitivity. References: Toussi SS, Pan N, Walters HM et al. Infections in children and adolescents with juvenile idiopathic arthritis and inflammatory bowel disease treated with tumor necrosis factor-α inhibitors: systematic review of the literature. Clin Infec Dis 2013;57:1318-30. Kleinert S, Tony HP, Krueger K et al. Screening for latent tuberculosis infection: performance of tuberculin skin test and interferon-γ release assays under real-life conditions. Ann Rheum Dis 2012;71:1791-5. Disclosure of Interest: None declared